2019
DOI: 10.1017/jfm.2019.421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pitch rate on freely translating perching airfoils

Abstract: We numerically investigated the unsteady dynamics of a two-dimensional airfoil undergoing a continuous, prescribed pitch-up motion and freely translating as a response to aerodynamic forces and the gravity field. The pitch-up motion was applied about an axis located $1/6$ chord away from the leading edge and was parameterized using the shape change number, with a Reynolds number set to 2000. It was shown that the minimum kinetic energy reached by the airfoil depends stochastically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The numerical method is further detailed in the works by 17 and 18 . It has been previously validated over a relatively large spectrum of low Reynolds number applications including axisymmetric bluff bodies 19 , revolving wings 20 and perching airfoils 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The numerical method is further detailed in the works by 17 and 18 . It has been previously validated over a relatively large spectrum of low Reynolds number applications including axisymmetric bluff bodies 19 , revolving wings 20 and perching airfoils 21 .…”
Section: Methodsmentioning
confidence: 99%
“…The numerical method used to solve the Navier-Stokes equations is further detailed in the works by [36,37]. It has been previously validated over a relatively large range of low Reynolds number applications including axisymmetric bluff bodies [38], revolving wings [39] and perching airfoils [40].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…They found that the significant lift and drag force on a wing during perching is mainly caused by the added mass effect and the formation of strong vortices at the leading and trailing edge of the wing. Jardin & Doué (2019) also performed a numerical study on a perching airfoil and concluded that a minimum kinetic energy could be achieved on the airfoil at the end of the perching manoeuvre at a higher pitch rate or the lift and drag force on the airfoil can be enhanced by increasing the pitch rate. Similarly, Fernando & Rival (2017) examined low-aspect-ratio plates undergoing deceleration and pitch-up motion.…”
Section: Introductionmentioning
confidence: 99%